Peace came in the form of a woman : Indians and Spaniards in the Texas borderlands - Barr, Juliana; William P. Clements Center for Southwest Studies (Chapel Hill : University of North Carolina Press, 2007)
Revising the standard narrative of European-Indian relations in America, Juliana Barr reconstructs a world in which Indians were the dominant power and Europeans were the ones forced to accommodate, resist, and persevere.
Diplomatic ritual in the "land of the Tejas" -- Political kinship through settlement and marriage -- Civil alliance and "civility" in mission-presidio complexes -- Negotiating fear with violence : Apaches and Spaniards at midcentury -- Contests and allianc
"Published in association with the William P. Clements Center for Southwest Studies, Southern Methodist University."
Includes bibliographical references (pages 347-388) and index.
Berkshire Conference of Women Historians Book Prize, 2007
NEW
Keywords: Indians of North America -- Texas -- History -- 18th century; Indian captivities -- Texas -- History -- 18th century; Spaniards -- Texas -- History -- 18th century; Missions, Spanish -- Texas -- History -- 18th century; Women and peace -- Texas -- History -- 18th century; Women -- Texas -- Social conditions -- 18th century; Diplomacy -- History -- 18th century; Texas -- History -- To 1846.; Prisonniers des Peuples autochtones -- Texas -- Histoire; Espagnols -- Texas -- Histoire; Missions espagnoles -- Texas -- Histoire; Femmes et paix -- Texas -- Histoire; Femmes -- Texas -- Conditions sociales; Diplomatie -- Histoire; Texas -- Histoire; Diplomacy; Indian captivities; Indians of North America; Missions, Spanish; Spaniards; Women and peace; Women -- Social conditions; Texas; To 1846; Indians of North America -- Texas -- History; United States, Texas -- Indigenous peoples -- History; United States, Texas -- Minorities -- History; pouvoir -- sexe (genre) -- Texas (Etats-Unis) -- 17e s. (fin) -- 18e s; History